Ujaran kebencian dalam pidato Marine La Pen - Nurdiansyah, Syalfila Putri; Asnidar, Yusi; Ismail, Subur (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2022)
Language has an important role in communication that is used every day. Without language, humans will find it difficult to understand each other. In the field of communication, there are many types of communication problems, one of which is hate speech. The spread of hate speech in everyday life is rife everywhere, both in cyberspace and in real life, which in this case is caused by the use of social media. The purpose of this study is to find out what types of hate speech are contained in Marine Le Pen's speech. This study is a qualitative study with a descriptive analysis approach and uses a listening and note-taking technique in collecting data. The data source used is a transcript of Marine Le Pen's speech for 2021-2022 as a campaign material in the French presidential election for the 2022-2027 period which is accessed through the official website mlafrance.fr. This study uses the theory of le Conseil de l'Europe to describe the types of hate speech, namely (1) Homophobia, (2) Antisemitism, (3) Sexism, (4) Xenophobia, (5) Islamophobia. The results of this study stated that there were 22 hate speech data with 15 data categorized as Xenophobic hate speech (68%) and 7 data categorized as Islamophobic hate speech (32%) in Marine Le Pen's speech. Meanwhile, there were no types of hate speech such as Homophobia, Antisemitism and Sexism. It also shows the political direction of Marine Le Pen as a politician from the right-wing party.